Postural balance, handgrip strength and mobility in Brazilian children and adolescents with osteogenesis imperfecta - Giovana Coêlho; Lívia Cocato Luiz; Luiz Claudio Castro; Ana C. de David (Elsevier, 2021)
Objective: To describe postural balance, handgrip strength and mobility in children and adolescents with different types of osteogenesis imperfecta. Methods: Cross-sectional study. Fifty selected subjects diagnosed with types I (n = 11), III (n = 21), and IV (n = 18), followed up at Brazilian reference center for osteogenesis imperfecta in the Midwest region, aged 2-21 years (9.2 ± 5.0), were enrolled in this study. Children and adolescents were evaluated for postural balance in the upright position with eyes-open and eyes-closed conditions, handgrip strength and the mobility domain (Pediatric Dysfunction Assessment Inventory). Data normality and difference between groups was verified. Results: Handgrip strength was significantly lower in people with type III of osteogenesis imperfecta when compared to the osteogenesis imperfecta types I and IV, and to the age-specific reference data. Center of pressure length and mean velocity in the condition with eyes closed were worse compared to the open-eyes condition for children and adolescents with type I of osteogenesis imperfecta. There were worse results in the mobility domain for the participants classified with the most severe type of osteogenesis imperfecta. Conclusions: It was observed that the severity of the osteogenesis imperfecta disease affected handgrip strength and locomotor function assessed by the mobility domain. Comparing osteogenesis imperfecta types, the higher the severity of osteogenesis imperfecta, the lower the handgrip strength. These results can contribute to new strategies of treatment focused on improving functional capacity and quality of life in people with osteogenesis imperfecta.